Comparative gene expression profiling of placentas from patients with severe pre-eclampsia and unexplained fetal growth restriction - Kurahashi Hiroki; Sekiya Takao; Kato Takema; Suzuki Machiko; Ota Sayuri; Nishizawa Haruki; Udagawa Yasuhiro (BMC, 2011)
Abstract Background It has been well documented that pre-eclampsia and unexplained fetal growth restriction (FGR) have a common etiological background, but little is known about their linkage at the molecular level. The aim of this study was to further investigate the mechanisms underlying pre-eclampsia and unexplained FGR. Methods We analyzed differentially expressed genes in placental tissue from severe pre-eclamptic pregnancies (n = 8) and normotensive pregnancies with or (n = 8) without FGR (n = 8) using a microarray method. Results A subset of the FGR samples showed a high correlation coefficient overall in the microarray data from the pre-eclampsia samples. Many genes that are known to be up-regulated in pre-eclampsia are also up-regulated in FGR, including the anti-angiogenic factors, FLT1 and ENG, believed to be associated with the onset of maternal symptoms of pre-eclampsia. A total of 62 genes were found to be differentially expressed in both disorders. However, gene set enrichment analysis for these differentially expressed genes further revealed higher expression of TP53-downstream genes in pre-eclampsia compared with FGR. TP53-downstream apoptosis-related genes, such as BCL6 and BAX, were found to be significantly more up-regulated in pre-eclampsia than in FGR, although the caspases are expressed at equivalent levels. Conclusions Our current data indicate a common pathophysiology for FGR and pre-eclampsia, leading to an up-regulation of placental anti-angiogenic factors. However, our findings also suggest that it may possibly be the excretion of these factors into the maternal circulation through the TP53-mediated early-stage apoptosis of trophoblasts that leads to the maternal symptoms of pre-eclampsia.